El control interno y la gestión administrativa en la Municipalidad Distrital de San Juan Bautista, Loreto 2023 - Romañola Elera, Everton Rayner (2024)
The objective of this final report was to determine the relationship between internal control and administrative management in the District Municipality of San Juan Bautista, Loreto 2023. To achieve this objective, an applied study at a descriptive - correlational level was carried out, using a non-experimental design. The study population was made up of 2,010 municipal workers, and a sample of 136 individuals was selected for data collection. The instrument used to collect data was a questionnaire. According to the results obtained, control is at a regular level, due to the promotion of ethical values by the institution, although sometimes the evaluation of risk management processes is not adequate. In addition, the identified risks are generally controlled and the procedures for obtaining internal and external information are followed. Although supervision and monitoring activities are carried out periodically, they are not always adequately controlled. For its part, administrative management presents an efficient performance, since institutional goals are mostly established properly, while institutional policies are sometimes half-defined. In general, corrective actions are almost always adopted in the face of identified variations, deviations and errors, which contributes to the development of activities. Determining that there is a positive and significant correlation between the variables, contrasted by a coefficient of 0.626 and a significance of 0.000.